2021
DOI: 10.1007/s11606-021-06959-3
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Trust in Government and Practice of Preventive Measures During the COVID-19 Pandemic in Japan

Abstract: Background Research suggests that preventive measures are critical to reducing the spread of coronavirus disease 2019 (COVID-19), but evidence regarding the association between trust in government and the practice of preventive measures is limited. Objective To examine whether the practice of preventive measures against COVID-19 differs by one’s level of trust in government. Design A cross-sectional analysis using the Japan COVID-19 and Socie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 22 publications
3
32
0
Order By: Relevance
“…Participants who answered “yes” or “somewhat yes” to the question, “Is the government trustworthy?” were defined as having trust in the government, while those who answered “no” or “not so much” were defined as having mistrust in the government. 21 We also included the response period (07/28–08/20, 08/21–08/24, or 08/25–08/31) as a potential factor influencing a respondent’s intention to get vaccinated, given that on August 19, 2021, the news reported that in Japan, a pregnant woman with COVID-19 went into preterm labor but was unable to find a hospital that could manage her; the woman delivered at home, which resulted in the death of her newborn. 22…”
Section: Methodsmentioning
confidence: 99%
“…Participants who answered “yes” or “somewhat yes” to the question, “Is the government trustworthy?” were defined as having trust in the government, while those who answered “no” or “not so much” were defined as having mistrust in the government. 21 We also included the response period (07/28–08/20, 08/21–08/24, or 08/25–08/31) as a potential factor influencing a respondent’s intention to get vaccinated, given that on August 19, 2021, the news reported that in Japan, a pregnant woman with COVID-19 went into preterm labor but was unable to find a hospital that could manage her; the woman delivered at home, which resulted in the death of her newborn. 22…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed data from the Japan "COVID-19 and Society" Internet Survey (JACSIS) study [26], a cross-sectional, web-based, self-reported questionnaire survey administered by a major nationwide internet research agency with 2.2 million qualified panelists [27][28][29]. Selected individuals aged 15 to 79 years (n=224,389) were included in the JACSIS study using stratified random sampling based on gender, age, and prefecture category to represent the distribution of the general population in Japan in 2019 [30,31]. Individuals who agreed to participate in the survey accessed the designated website and responded to questionnaires asking about a wide range of socioeconomic, lifestyle, and health measures in the context of the COVID-19 pandemic.…”
Section: Study Design Setting and Data Sourcesmentioning
confidence: 99%
“…Institutional trust is pivotal in protecting subjective well-being during pandemics and disasters [ 6 , 10 , 11 ]. However, the mechanisms through which institutional trust relates to or influences subjective well-being in the context of the COVID-19 crisis remain unclear.…”
Section: Introductionmentioning
confidence: 99%